BOARD DIVERSITY AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURES - Lucky Lestiananda; Yeterina Widi Nugrahanti; Gracella Theotama (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
Companies in Indonesia still don't care enough about Corporate Social Responsibility (CSR) causing various kinds of problems. Whereas, CSR is a form of corporate responsibility to stakeholders. This study aim to examine the effect of board diversity on the disclosure of CSR. All manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2020 are used for population of this study. This study used quantitative approach and multiple linear regression analysis. Based on the results of testing of hypotheses, it is found that gender diversity, educational background diversity, and board size diversity have no effect on CSR disclosure. Then, tenure diversity and age diversity have a positive effect on CSR disclosure. Control variables in this study are company size and profitability. While company size has a positive effect and profitability has no effect on CSR disclosure. The results of this study can be used materials for improvements related to CSR disclosure in manufacturing companies.